ANALISIS PENGARUH KUALITAS SPARE PART TERHADAP KEPERCAYAAN KONSUMEN PADA PT BOSOWA BERLIAN MOTOR KOTA KUPANG - Rey Rivalda Rodjo Wadu; David R.E Selan; Marselinda Hege (P3M Politeknik Negeri Ambon, 2026)
This study aims to analyze the effect of spare part quality on consumer trust at PT Bosowa Berlian Motor Kupang. The research was motivated by the increasing importance of consumer trust in the automotive industry, especially in the provision of high-quality spare parts by authorized dealers. Consumer trust is considered a strategic factor that can influence purchasing decisions and long-term relationships between companies and customers. The study focused on the relationship between spare part quality as the independent variable and consumer trust as the dependent variable. This research employed a quantitative approach using a simple linear regression analysis method. Data were collected through questionnaires distributed to consumers of PT Bosowa Berlian Motor Kupang. The population consisted of customers who had purchased vehicles and spare parts within the last six months, with a sample of 71 respondents selected using purposive sampling. The variables were measured using a Likert scale consisting of indicators related to product quality, durability, product superiority, warranty, and consumer trust. The results showed that the quality of spare parts had a positive and significant effect on consumer trust. Consumers perceived that spare parts with good quality, durability, reliability, and guaranteed authenticity contributed to increasing their confidence in the company. The findings indicate that improving spare part quality can strengthen consumer trust and support the company’s competitiveness in the automotive market. Keywords: spare part quality; consumer trust; automotive industry; product quality; PT Bosowa Berlian Motor Kupang